Comparison of survival outcomes in optimally or maximally cytoreducted stage IIIC ovarian high-grade serous carcinoma: women with only peritoneal tumor burden versus women with both peritoneal and lymphogenous dissemination. (1st November 2019) - Selcuk, I; Meydanli, MM; Yalcin, I; Gungorduk, K; Akgol, S; Celik, H; Ayhan, A
Abstract : Introduction/Background: The aim of this study was to analyze the survival outcomes of stage IIIC ovarian high-grade serous carcinoma (HGSC) patients with both peritoneal and lymphatic dissemination (IP(+)/RP(+)) who had undergone maximal or optimal cytoreduction followed by intravenous carboplatin/paclitaxel chemotherapy to those women with stage IIIC ovarian HGSC who have only peritoneal involvement (IP(+)/RP(-)) treated similarly. Methodology: We performed aretrospective, multicenter study by participation of five gynecologic cancer centers. At first, stage IIIC ovarian HGSC patients were classified asoptimally or maximally debulked cohorts. Then in each cohort, patients were divided into two groups: The IP(+)/RP(–) group included women with transcoelomic spread outside the pelvis with no nodal disease, The IP(+)/RP(+) group included patients with transcoelomic dissemination outside the pelvis in addition to positive nodal status. Survival outcomes were compared between the two groups in each cohort. Results: A total of 405 ovarian HGSC patients were analyzed. In the optimally debulked cohort (n=257), the median progression-free survival (PFS) and overall survival (OS) for the IP(+)/RP(-) group (n=69) was 24 and 57 months, respectively compared to 21 and 58 months in the IP(+)/RP(+) group (n=188) (p=0.78, and p=0.40; respectively). In the maximally debulked cohort (n=148), the median PFS and OS for the IP(+)/RP(-) group (n=55) was 35 and 63 months, respectively compared to 25 and 51 months in the IP(+)/RP(+) group (n=93) (p=0.49, and p=0.31; respectively). Conclusion: Our findings indicated no survival difference between the IP(+)/RP(-) and the IP(+)/RP(+) groups after maximal or optimal cytoreduction. Disclosure: Nothing to disclose.